Anti‐Arrhythmic Effects of Linalool via Cx43 Expression in a Rat Model of Myocardial Infarction - Ke, Jianlin; Zhu, Canzhan; Zhang, Yuanyuan; Zhang, Wenlong (Frontiers in Pharmacology, 2020)
Background: Lavender is a traditional therapy for different heart symptoms including palpitation, which comprises an important symptom of cardiac arrhythmias. This experiment was designed to evaluate the antiarrhythmic effects of linalool using an experimental model of arrhythmia following myocardial infarction in rats. The underlying electrophysiological mechanism through cardiac connexin 43 (Cx43) expression was also investigated. Methods: Fifty male Sprague-Dawley rats were divided into five equal groups. The first group was considered as the normal control group; MI was induced by ligation of the left anterior descending artery (LAD) in the second group. The other three groups received metoprolol (100 mg/kg/day) or linalool (50 or 100 mg/kg/day) for seven days before LAD ligation. The arrhythmia score, isolated myocyte resting potential, histological changes, and cardiac Cx43 expression levels were evaluated. Results: In the MI group, there was a significant increase in the arrhythmia score but a marked decrease in resting membrane potential relative to the control; these changes were prevented by the administration of metoprolol or linalool. The histological changes were also minimized in the groups treated with these substances compared to the untreated MI group. The western blot and real-time PCR results showed that the protein expression of Cx43 in the infarct zone of the rat hearts was significantly higher in the MI groups receiving metoprolol or linalool compared with the untreated MI group. Conclusion: Linalool was shown to be able to dose-dependently decrease the incidence of arrhythmias in a rat model of myocardial infarction. We propose that the key mechanism behind this antiarrhythmic effect is probably the prevention of decreased Cx43 expression following MI.